DETERMINATION OF THE ACTIVITY OF NANO COATED CONJUGATED LINOLENIC ACID ON THE CHEMICAL COMPOSITION OF CHEESE - Shahba Rafe Abdullah; Mohammad Ahmad Jassim; Rafid Khalil Abdul Rezzaq (Scholar Express Journals, 2022)
This study was conducted to evaluate the effect of conjugated Nano- and NonNano-coated linolenic acid on the chemical composition of cheese during different storage periods. C1 = control and cheese sample with added linolenic acid at a concentration (100 mg/kg), C2 and , cheese sample with added linolenic acid with a concentration of (200 mg / kg) C3 and cheese sample with added uncoated linolenic acid at a concentration (100 mg / kg) C4 and cheese sample with added cheese Uncoated linolenic acid at a concentration of (200 mg/kg) C5, and the results of storing cheese showed that the moisture content decreased significantly (p<0.05) until the end of the storage period, and the treatment C3 was less in moisture loss (58.96%). It was also found that the percentages of protein, fat and ash did not show significant differences at the time of one day compared with the control sample C1, then these percentages gradually increased as the preservation period was prolonged and reached their highest values at the time of 21 days. As for the pH values, it decreased significantly to be at the end of the storage period between (6.30- 6.45) compared with the control sample was 6.05 and it was found that the values of fatty acids for all treatments were significantly lower compared with the control treatment C1 at the time of one day, and the percentage of acids increased The free fatty acids reached their highest values between (0.55-0.13)% for all treatments compared to the control treatment C1 at the end of the storage period, which amounted to 1.25%.
Keywords: cheese; nanotechnology; chemical composition; control sample